Allogenic Cultured Limbal Epithelial Transplantation and Cultivated Oral Mucosal Epithelial Transplantation in Limbal Stem Cells Deficiency: A Comparative Study - Mohamed Elalfy; Kareem Elsawah; Sundas Maqsood; Nigel Jordan; Mansour Hassan; Ahmed Zaki; Zisis Gatzioufas; Samer Hamada; Damian Lake (Ophthalmology and Therapy)
Abstract Introduction This study compared the clinical outcomes of allogenic cultured limbal epithelial transplantation (ACLET) and cultivated oral mucosal epithelial transplantation (COMET) in the management of limbal stem cell deficiency (LSCD). Methods Forty-one COMET procedures in 40 eyes and 69 ACLET procedures in 54 eyes were performed in the Corneoplastic Unit of Queen Victoria Hospital, East Grinstead. Data were examined for demographics, indications, ocular surface stability, absence of epithelial defect, ocular surface inflammation, visual outcomes, and intra- and postoperative complications. Results Kaplan–Meier analysis showed that patients in the ACLET group with longer follow-up had a significantly higher graft survival rate (81.7%, n = 56) than the COMET group (60.7%, n = 25) and the difference was statistically significant (p = 0.01). In the COMET group, there was no statistically significant improvement in the visual acuity (VA) while in the ACLET group there was statistically significant improvement in the final VA. Elevated intraocular pressure (IOP) developed in 9 eyes (22.0%) in the COMET group and in 18 eyes (26.1%) in the ACLET group; infection developed in 4 eyes (9.8%) in the COMET group and in 10 eyes (14.5%) in the ACLET group; and perforation or melting happened in 4 eyes (9.8%) in the COMET group and in 1 eye (1.4%) in the ACLET group. Postoperative immunosuppression complications were noted in 9 eyes (13.0%) in the ACLET group. No graft rejection was observed in either group. Conclusion Both ACLET and COMET are effective therapeutic procedures for managing advanced and bilateral cases of LSCD. Although COMET has lower graft survival rate than ACLET, it does not mandate systemic immunosuppression therapy to protect against potential graft rejection.